Functional outcome of single bundle anatomical anterior cruciate ligament reconstruction using either quadruple hamstring or bone patellar tendon bone graft by medial portal technique - Thapa , SS; Neupane , P; Lamichhane , AP; Mahara , DP (Journal of Institute of Medicine Nepal, 2018)
Introduction: The anterior cruciate ligament (ACL) is the most frequently injured knee ligament. Abnormal knee kinematics in ACL deficient knee causes early osteoarthritis. Single bundle anatomical ACL reconstruction by medial portal technique provides better knee stability then transtibial technique. Many studies suggests that there is no difference in outcome of ACL reconstruction using hamstring or bone patellar tendon autograft. In this study we evaluated functional outcome (based on mean Lysholm score) at 6 month of single bundle ACL reconstruction by medial portal technique using bone patellar tendon bone or quadruple hamstring graft Methods: This was a prospective longitudinal study on functional outcome (using Lysholm score) of 75 patients who underwent single bundle anatomical ACL reconstruction by medial portal technique by using either quadruple graft hamstring or bone patellar tendon bone graft in sports and arthroplasty unit in Tribhuvan University teaching hospital, Kathmandu, Nepal between March 2014 to February 2016. Mean Pre op and 6 months post op Lysholm score of two groups was compared using paired-t test to evaluate the functional outcome of the surgery. Results: In this study overall mean pre op Lysholm score was 48.48±6.50 (36-62) and 6 months post op Lysholm knee score was91.58±3.10 (85-95), with p value 0.0000. The mean pre op and post op Lysholm score for Quadruple hamstring group was 47.7 and 91.5 respectively, while that for bone patellar tendon bone group was 54 and 91.7. Conclusion: The functional outcome (based on mean Lysholm score) at 6 months post op of single bundle anatomical ACL reconstruction was similar irrespective of type of graft used.